Efektivitas Pelayanan Kesehatan di Puskesmas Jumpandang Baru Kota Makassar - Tetty Dwiyanti; Adina astari (YUME : Journal of Management, 2020)
AbstractPuskesmas  Jumpandang  Baru Makassar  City. This study aims to obtain a picture of the effectiveness of health services at Puskesmas Jumpandang  Baru Makassar City and to know the factors that affect the effectiveness   of   health   services   at   Puskesmas   Jumpandang   Baru Makassar  City.  To  answer  the  problem  of  research,  used  descriptive research  method with  qualitative  approach.  Data collection  is done  by observation, interview and documentation. In addition, data collection also uses   data   analysis   techniques   by  collecting,   data   reduction,   data presentation and conclusions. The  effectiveness  of  health  services  at  Puskesmas  Jumpandang Baru Makassar City is in accordance with indicators used to measure the effectiveness of health services such as achievement of goals, integration, adaptation,  and commitment   Factors that  influence the effectiveness  of health services in Puskesmas Jumpandang Makassar City such as organizational characteristics, environmental characteristics, worker characteristics and managemant characteristics. Keywords: Effectiveness   and management